Effects of Reservoir Levels on Arizona National Recreation Area Visitation, Visitor Spending, and Local Economies. (31st October 2021) - Duval, Dari; Bickel, Ashley K.; Frisvold, George B.
Abstract: This study estimates the effects of reservoir levels on demand for recreation visits to Lake Powell (Glen Canyon National Recreation Area [NRA]) and Lake Mead NRA, correlating reservoir levels with overnight and total recreation visits. We also consider the effects of closures of recreation access points (such as launch ramps or marinas) when lake levels fall below critical thresholds. Our overall results are similar to past studies, but find that the access point closures are a more robust predictor of visits than simple elevation measures. Policies that manage the Colorado River, including those that seek to maintain reservoir levels above critical levels with the primary goal of preventing water delivery cutbacks, also affect recreation demand and the economies of nearby communities. Our analysis maps changes in visits (from changing elevations) to changes in visitor spending, recreationist user benefits, and regional economic indicators such as value added and employment. Such indicators could be used in future benefit‐cost or economic impact analyses of Colorado River water management policies.